Prenatal Risk Factors on Children’s Cerebral Palsy Case at RSIA Bunda Jakarta - Banatul Banatul Lariza; Kurnia Dwi Artanti; Taufiq Taufiq Hidayat (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Introduction: Cerebral Palsy is a disease that is less recognized by the public due to the lack of information related to CP in Indonesia. Aims to analyze prenatal risk factors that influence the evidence of CP RSIA Bunda Jakarta.Methods: This study was conducted in April 2021 at RSIA Bunda Jakarta, an analytical study with a case control design. The sample in this study were 124 respondents from mothers of children who underwent outpatient treatment at the RSIA Bunda Jakartaas cases and controls. each taken by simple random sampling technique. Data were analyzed using the test chi-square to analyze the relationship between variables.Results: The results of statistical analysis showed that the risk factors associated with the incidence of CP were maternal age (p= 0.00; OR= 13.25; 95% CI= 2.93-59.93), preeclampsia (p= 0.00; OR= 2,06; 95% CI= 1,71-2,48), TORCH (p= 0.00; OR= 2.40; 95% CI= 1.92-3.01), and antenatal care (p= 0.00; OR= 41.2; 95% CI= 5.45-317.0). Conclusion: Risk factors affecting the occurrence of CP in children include age <20 or ≥35 years, preeclampsia, TORCH infection and antenatal care visits <4 times. It is necessary to increase intervention programs at various levels of health services to diagnose and prevent the occurrence of cerebral palsy in children so that optimal maternal and child health is achieved. and further research is needed to determine other risk factors that can cause CP in children such as perinatal and postnatal risk factors.